Hambatan Pendidik IPA Kelas VII dalam Mengimplementasikan Kurikulum 2013-Revisi - Derra Meiasri Putri; Darlen Sikumbang; Rini Rita T Marpaung (Universitas Lampung, 2019)
This study aims to describe the barriers of class VII science educators in implementing the K13-revision in the Bandar Lampung Municipality. The sample of this study were all VII grade science educators who applied K13-revision learning. Sampling technique was that purposive sampling. Data were obtained from was questionnaires and interviews that were analyzed descriptively. The results showed that the implementation revised K13 in the 2016/2017 school year in of Bandar Lampung little experiecing obstacles, there were three aspects form four which according to science teacher, that were: (1) information about the revised 2013 curriculum; (2) learning texts; and (3) the learning process with a percentage range of 25%-50%. Aspects that show of obstacles to the process and implementation of the assessment had 63% of aspects in the category of